Functional characterisation of molbdopterin synthase-encoding genes in mycobacteria - Narrandes, Nicole Collette (My University, 2014)
Mycobacterium tuberculosis (Mtb) possesses a complete repertoire of genes for the biosynthesis of molybdopterin cofactor (MoCo). The multi-step biosynthetic pathway in Mtb is distinguished by the fact that it displays a multiplicity of homologues of several genes, most notably those involved in the second step, which include moaD1, moaD2, moaE1, moaE2 and moaX. The moaD and moaE genes encode the small and large subunits of the molybdopterin (MPT) synthase enzyme respectively, whereas moaX encodes a novel fused MPT synthase which contains both MoaD and MoaE functional domains. This study aimed to assess the function of these multiple homologues and their relative contributions to MoCo biosynthesis in Mtb and to investigate the role of post-translational processing in MoaX function. In addition, the contribution of two Mycobacterium smegmatis MoCo-dependent nitrate reductase (NR) enzymes, the putative assimilatory NarB and the respiratory NarGHI, to nitrate assimilation was investigated. Derivatives of the MoCo-deficient M. smegmatis ΔmoaD2 ΔmoaE2 double mutant were generated carrying all possible combinations of the Mtb moaD and moaE genes to assess the ability of these genes to complement the growth phenotype when expressed in this heterologous host. MoCo biosynthesis was monitored by the ability to grow in minimal media containing nitrate as a sole nitrogen source (MPLN), facilitated by a MoCo dependent assimilatory NR. Complementation studies showed that only the moaD2 moaE2 combination of Mtb genes are able to restore growth of the M. smegmatis double mutant in MPLN when introduced on multi-copy plasmid, pointing to a functional hierarchy in MPT synthase encoding genes in Mtb. Furthermore, the fused MPT synthase, MoaX, was shown to be cleaved at a glycine residue (Gly81), corresponding to the penultimate glycine in MoaD homologues; this process is essential for MPT synthase activity. Site-directed mutagenesis was used to show that another glycine residue in MoaX (Gly82), corresponding to the terminal glycine residue of MoaD homologues, is crucial for MoaX function. Together, these data suggest that MoaX functions as a canonical MPT synthase. Phenotypic characterization of the NR-deficient mutants, ΔnarB, ΔnarGHJI and ΔnarB ΔnarGHJI, revealed that the loss of both NarB and NarGHI did not alter the organisms ability to grow in MPLN, suggesting either that M. smegmatis possesses additional MoCo-dependent enzymes which are able to catalyze the reduction of nitrate to nitrite or an alternate nitrate assimilation pathway exists. In summary, this study has provided new insights into the biosynthesis of a key mycobacterial cofactor, which may contribute to the development of improved strategies to combat tuberculosis.